Prevalence of therapeutic use exemptions at the Olympic Games and Paralympic Games: an analysis of data from 2016 to 2022 - Vernac, A.; Healy, D.; Banon, T.; Petroczi, A. (British Journal of Sports Medicine, 2024)
Objectives The objectives of this study are to describe the prevalence of therapeutic use exemptions (TUEs) among athletes competing in four Olympic and four Paralympic games. The secondary objective was to present the prohibited substance and methods classes associated with TUEs.